Critical Discourse Analysis: Theoritical Framework - Hidayah, S.S, M.A, Arini; Anindhita, Widyashanti Kunthara (JURNAL PENDIDIKAN, 2022)
When we discuss critical discourse analysis, we are not only talking about assertions, but also about the structure and principles of discourse. Discourse principle and critical discourse analysis structures cannot be divorced from the connection or relationship between discourse and reality. The term "reality" refers to a collection of social creations established through discourse. The discourse analysis discussed in this paper will establish a foundation for understanding discourse as something other than a subject of language study, but as an intentional social practice. Discourse does not always occur in this manner, but has a definite goal intended to be communicated to the listener. It is not sufficient to evaluate the language parts alone while undertaking discourse analysis; one must additionally consider the context in which the speech is constructed. Not only does critical discourse analysis evaluate language in terms of linguistic studies or isolated parts of language, but it also analyzes language in relation to its environment. The context indicates that the language is being utilized for specific purposes and behaviors